Extant virtual lab. technology is used in teaching chemistry course in secondary schools in inclusive learning environment from the teachers’ perspectives - Al-Harhty, Mona Mafarh DhakeelAllah; Al-Arini, Hanan AbdulRahman (Journal of Educational and Psychological Sciences, 2023)
The research aimed at Identifying to what extant virtual lab. technology is used in teaching chemistry course in secondary schools in inclusive learning environment from the teachers’ perspectives. The researcher used Survey Descriptive Approach. The study sample consisted of (207) chemistry female teachers at the secondary schools in Riyadh, school year 1443/ 2022. For data collection, the research instrument was a questionnaire. The study concluded to a set of findings including: course in secondary schools in inclusive learning environment is at the mean of (3.85), a highly convenient degree. Challenges face activating virtual lab. technology in teaching chemistry course in secondary schools in inclusive learning environment is at the mean of (4.05), a highly convenient degree. And that one of the most important solutions to overcome the obstacles that prevent the activation of virtual laboratory technology in teaching the chemistry course in the secondary stage in the integrated education environment is to prepare courses that enable teachers and students to use virtual laboratories, develop a guide for use, and provide infrastructure from devices, internet and programs in Arabic that can be downloaded On all operating systems and in light of the search results, the two researchers made recommendations, the most important of which are: taking advantage of global experiences in training teachers on the skills of using virtual laboratories in chemistry. The development of chemistry curricula in the secondary stage, and the compositions include some practical parts that use virtual laboratory technology.